Magnetic resonance imaging as a diagnostic method - Ręba, Patrycja (Journal of Education, Health and Sport, 2021)
Admission In human medicine, magnetic resonance imaging (MRI) is one of the leading and most popular diagnostic methods. In veterinary medicine, initially, MRI was treated mainly as a research tool, but with the development of veterinary specializations, an increase in the number of specialists, reference clinics, but also an increase in awareness and expectations of animal owners, MRI began to play a key role in the clinical practice of small animals - dogs and cats , exotic animals and horses. Aim The aim of the study is the analysis of magnetic resonance as a diagnostic method. Material and method Review of the available literature on the subject. Results Magnetic resonance imaging is based on the phenomenon of nuclear magnetic resonance, characteristic of the nuclei of elements with an odd number of protons or neutrons, and therefore having a momentum (spin) and a magnetic moment. The most commonly used element is the hydrogen atom, thanks to its richness in living organisms. The general scheme of how MRI works is a five-step process involving the following phenomena: Placing the patient in a constant homogeneous electromagnetic field Radio frequency (RF) signal emission Interruption in RF signal emission RF feedback by the body Processing of the emitted signal and image reconstruction. Currently, the most popular areas of research are the central nervous system (brain and spine) and the musculoskeletal system. The test allows you to diagnose intracranial diseases such as: birth defects, inflammatory changes in the brain tissue, demyelinating diseases or cancer. Conclusions The versatility of magnetic resonance imaging, both in terms of species diversity (small animals, horses, exotic animals) and imaging areas (central and peripheral nervous system, bones with their joints, muscle tissue) has made MRI a very important method diagnostic used in clinical veterinary medicine. The other advantages of magnetic resonance imaging include imaging in three planes, enabling subsequent three-dimensional reconstruction, no harmful X-rays and the possibility of using contrast agents.